Firms horizontal mergers and product differentiation strategies - Méndez Naya, José (Estudios de Economía, 2017)
Taking as a reference a simple oligopoly model with differentiated products, in which there are three firms, the purpose of this paper is to complement the existing literature on mergers by proving that the traditional merger paradox can be avoided by assuming that, after the merger, the merging firms increase the existing bilateral product differentiation. In this context, it is proved that a merger could be welfare enhancing by increasing both consumers surplus and merging and non merging firms profits.